Pendampingan Hukum Waris Bagi Anak Yatim di Yayasan Dapur Dhuafa Indonesia Kunciran Indah Kecamatan Pinang Kota Tangerang - Endang Sutisna (Jurnal Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to provide comprehensive education and understanding regarding the inheritance rights of orphans at the Dapur Dhuafa Indonesia Foundation, Kunciran Indah, Pinang District, Tangerang City. The activity methods used included problem identification, socialization through legal counseling, and evaluation of participants' understanding. The results of the activity showed that participants gained increased knowledge regarding the inheritance rights of orphans, inheritance distribution mechanisms according to the Compilation of Islamic Law, and legal steps that can be taken in the event of a dispute. Supporting factors for the activity included the active participation of the foundation's management and the enthusiasm of the participants, while obstacles that emerged were the participants' limited initial understanding and the lack of legal documents related to the heir's assets. With this assistance, it is hoped that the inheritance rights of orphans can be better protected, and the surrounding community will become more aware of the need to participate in protecting and fighting for their rights